Visfatin levels in non-obese, obese, and insulin resistant adolescents - Indra Ihsan; Eka Agustia Rini; Rismawati Yaswir (Indonesian Pediatric Society, 2016)
Background Adipose tissue is not merely a site for energy storage, but is also the largest endocrine organ, secreting various adipocytokines. Plasma visfatin, an adipocytokine predominantly secreted from visceral adipose tissue, has insulin-mimetic effects, and has been closely linked to insulin resistance.Objective To compare plasma visfatin levels between obese and non-obese adolescents, as well as between obese adolecents with and without insulin resistance.Methods This cross-sectional study was conducted in students who attended three senior high schools in Padang. Subjects comprised 28 obese and 28 non-obese adolescents. The age of the subjects ranged from 14-18 years. Obesity criteria were based on body mass index (BMI) measurements. Fasting serum glucose level was measured by glucose hexokinase photometry and serum insulin was measured by chemiluminesence immunoassay. Plasma visfatin was measured by enzyme-linked immunosorbent assay (ELISA). The insulin resistance index was estimated from fasting serum insulin and glucose levels using the homeostatic model assessment for insulin resistance (HOMA-IR). Differences in the variables were tested using independent T-test and Mann-Whitney test, depending on the distribution of the variables.Results The mean plasma visfatin level was significantly higher in the obese than in the control group [2.55 (SD 1.54) vs. 1.61 (SD 0.64) ng/mL, respectively; (P=0.005)]. The insulin resistant group had significantly higher mean plasma visfatin level than the non-resistant group [3.61 (SD 1.59) vs. 1.96 (SD 1.18) ng/mL, respectively; (P=0.004)].Conclusion Obese adolescents with insulin resistance have signifcantly higher plasma visfatin levels compared to those without insulin resistance.